Arresting Development: Convictions of Innocent Youth Symposium 2010: Righting the Wronged: Causes, Effects, and Remedies of Juvenile Wrongful Conviction - Tepfer, Joshua A.; Nirider, Laura H.; Tricarico, Lynda M. (Rutgers Law Review, 2009)
Disclaimer: This summary was generated by AI based on the content of the source document.